Reprography, Micrography, and Visual Communication Technology: An Outline - Nagarajan, K. S. (Journal of Information and Knowledge, 2014)
Discusses the developments in reprography, micrography and visual techniques in transfer of information. The value of exact and compact storage of information is identified. Suggests a full fledged specialisation in these fields. Outlines a course module for Library and Information professionals at the B.Lib. Sc level as well as M.Lib. Sc level.